2006
DOI: 10.2527/2006.844807x
|View full text |Cite
|
Sign up to set email alerts
|

Feed efficiency of rainbow trout can be improved through selection: Different genetic potential on alternative diets1

Abstract: To assess the genetic potential for selection of increased feed efficiency in rainbow trout (Oncorhynchus mykiss), we estimated the heritabilities and correlations for BW, daily weight gain (DG), and daily feed intake (DFI). Body weight was recorded 5 times, and DG and DFI 3 times during a feeding trial lasting 22 mo. To test the hypothesis that phenotypic and genetic parameters were influenced by a nutritional environment, fish were fed either a modern normal protein diet (NP, 40 to 45% protein and 30 to 33% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 30 publications
(51 reference statements)
5
66
2
1
Order By: Relevance
“…However, because of the genetic Selection for residual feed intake in fish structure of our population (genetically identical fish and a single dam common to all individuals), this value cannot be compared with data found in the literature. Few studies have assessed genetic variability of feed efficiency in fish [15,21,23,33,36,39]. Among these only one study gives precise differences in RFI among families and individuals [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the genetic Selection for residual feed intake in fish structure of our population (genetically identical fish and a single dam common to all individuals), this value cannot be compared with data found in the literature. Few studies have assessed genetic variability of feed efficiency in fish [15,21,23,33,36,39]. Among these only one study gives precise differences in RFI among families and individuals [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of growth selection on feed efficiency is disputed. While Kause et al [21] have found that rapid growth in rainbow trout (Oncorhynchus mykiss) is related to high feed efficiency, Mambrini et al [27] have not detected any improvement in feed efficiency when selecting brown trout (Salmo trutta) for growth gain. Hence at least in brown trout, selection on growth does not necessarily lead to improvement in feed efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It was purely intended to act as a challenge environment to optimising the genetic response of traits such as protein and growth efficiency in salmonids [21,22,27]. However, as a long-term study, it has enabled us to investigate the effect of dietary protein on skeletal growth (length), which is important knowledge for future production of fish with high growth performance quality [32] as well as for future growth study in natural ecosystems where protein deposition is the main cause [12].…”
Section: Discussionmentioning
confidence: 99%
“…To calculate genetic response in FE, mean FE was first calculated for each diet from the data, i.e., before selection. Then, genetic responses to selection were calculated for DG and DFI, and the new mean FE was calculated from these [22].…”
Section: Prediction Of Genetic Responses To Selectionmentioning
confidence: 99%
“…Breeding programmes exist for all major farmed carnivorous fish species, and have achieved improvements in growth, feed efficiency, disease resistance and product quality traits [12]. Improved feed efficiency in particular is a goal of most fish breeding programmes, but genetic parameter estimates for feed consumption and efficiency are rare [21,22,24,42]. This is because recording methods for individual fish feed intake have only recently been implemented in large-scale genetics research [21,22,42]; thus no current breeding programmes select directly for feed efficiency.…”
Section: Introductionmentioning
confidence: 99%